Corporate Governance and Corporate Behavior in Japan The Consequences of Stock Options and Corporate Diversification - Hanazaki, Masaharu (Development Bank of Japan Research Series, 2016)
This book carefully examines the effects of changes in the corporate governance structure on corporate behavior or company performance, using micro-data from listed companies in Japan. The author found that in Japan the introduction of stock options had neither a positive impact on profitability nor the negative side effects of promoting risk-taking behaviors. Furthermore, he found that corporate diversification and division of corporations showed negative impacts on profitability. The corporate governance structure of Japan has exhibited a large change from the second half of the 1990s to the present. There have been institutional reforms involving enterprise law, such as the introduction of stock options and the removal of the ban on holding companies. With respect to the ownership structure of a company, discernible trends are that the equity holdings of financial institutions and business corporations have fallen while the presence of foreign stockholders has risen. These trends are often pointed out as signs that the Japanese corporate governance structure has been approaching the American model and that this will energize Japanese firms. The author contradicts common academic theories, however, and concludes that the formation of the corporate governance which emphasizes the agency problem between shareholders and corporate managers is inadequate. He suggests that an institutional arrangement for a corporate governance system that values a variety of stakeholders' interests is greatly needed and concludes that perspectives on maximizing surplus values for various stakeholders and distributing the surpluses appropriately among the stakeholders will become increasingly important for the purpose of managing corporations.